FORMING THE LEADERSHIP QUALITIES OF HIGH SCHOOL STUDENTS - Kunytsia, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article deals with the problem of developing leadership qualities of high school students. The purpose of the study is to analyze theoretically the problem of developing leadership qualities of high school students, to determine the basic competencies of teachers necessary for their formation. The main tasks are as follows: to analyze the scientific literature on the problem of developing leadership qualities of high school students; to reveal the socio-psychological and pedagogical features of the development of leadership qualities of high school students; to formulate recommendations for the formation of student teachers' readiness to develop leadership qualities of high school students. To determine the state of development and prospects of the researched problem research, the following research methods were used: theoretical methods (analysis of regulatory documentation, study of socio-pedagogical, psychological scientific research; comparison of different scientific views on the research problem; systematization and generalization of acquired knowledge), and empirical methods (determination of socio-psychological and pedagogical conditions for the development of leadership qualities) The article analyzes the scientific and methodological literature on the research topic, determines the state of development and prospects of the research topic; conducts a comparative analysis of scientific approaches to the phenomenon under study; systematizes and generalizes the knowledge gained; identifies the professional competencies required by teachers, which are key to the development of leadership skills in high school students. These competencies are: knowledge of leadership; communication skills; understanding of individual needs of students; facilitation skills. According to the results of the study, it was determined that the formation of leadership qualities in high school students requires an individual approach; it requires teachers to understand their socio-psychological and pedagogical characteristics and can be realized by stimulating students' independence and responsibility, organizing situations favourable for the development of leadership qualities, and developing communication and cooperation skills. All these social and pedagogical aspects require constant analysis and updating of methods of working with high school students. Only this way, it will be possible to develop students’ leadership qualities successfully, as well as promote their further development and adaptation in a dynamically changing society.